If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 30 + -10(2n + 4) = 6(7n + 2) + -29n Reorder the terms: 30 + -10(4 + 2n) = 6(7n + 2) + -29n 30 + (4 * -10 + 2n * -10) = 6(7n + 2) + -29n 30 + (-40 + -20n) = 6(7n + 2) + -29n Combine like terms: 30 + -40 = -10 -10 + -20n = 6(7n + 2) + -29n Reorder the terms: -10 + -20n = 6(2 + 7n) + -29n -10 + -20n = (2 * 6 + 7n * 6) + -29n -10 + -20n = (12 + 42n) + -29n Combine like terms: 42n + -29n = 13n -10 + -20n = 12 + 13n Solving -10 + -20n = 12 + 13n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-13n' to each side of the equation. -10 + -20n + -13n = 12 + 13n + -13n Combine like terms: -20n + -13n = -33n -10 + -33n = 12 + 13n + -13n Combine like terms: 13n + -13n = 0 -10 + -33n = 12 + 0 -10 + -33n = 12 Add '10' to each side of the equation. -10 + 10 + -33n = 12 + 10 Combine like terms: -10 + 10 = 0 0 + -33n = 12 + 10 -33n = 12 + 10 Combine like terms: 12 + 10 = 22 -33n = 22 Divide each side by '-33'. n = -0.6666666667 Simplifying n = -0.6666666667
| 2x-47=+(-x)+19 | | y=6x+19 | | 6m-2m-m= | | 2[n-(4n+22)+10]=2(n+12) | | 87-2x=7-10x | | M^2+4m-28=0 | | 14n+-7n-n=-18 | | 2x+3.2=5.6 | | -39=-55+v | | 2(x+1)-4x= | | 2x-12=23 | | 3(2x-4)-6(2x-1)= | | -14=10-g | | 5f-1=6+3f | | 12-3x=-5x+18 | | 2c+2(c-6)=24 | | -8b+18b-9b=-13 | | (4x^3-11x-10)/(x-2) | | 7.9+x=0.6 | | 7(5.5)+3(5.5)+5(5.5)+187.5=225 | | 7(2.5)+3(2.5)+5(2.5)+187.5=225 | | 4m-2=-3m-39 | | 31=4+x | | (y^6z^9)(6y^4z^2)= | | 7(3.5)+3(3.5)+5(3.5)+187.5=225 | | 4m-2=-3-39 | | 7(4.5)+3(4.5)+5(4.5)+187.5=225 | | -13+x-3=15-17+1 | | 3x+9=-21-2x | | -0.5(0.3x-.6)=-1.5 | | 13n+12n+-15n+-4n+-2n=-20 | | 9g-5=50 |